Utilização do gesso para fabricação de artefatos alternativos, no contexto de produção mais limpa - Munhoz, Fabiana Costa [UNESP] (Universidade Estadual Paulista (Unesp), 2008)
In Brazil, the activities of civil construction are an issue of great concern to the environmental leaders, particularly in relation to the generation and management of the construction wastes. Given the need for sustainable development in this sector, technological innovation has become an important tool for the mitigation of environment impacts. Based on the principles of cleaner production (P + L), the aim of this work was to collaborate to the develoment of technological innovation in civil construction, aiming to reduce the waste generated in constructions. Plaster, water and polymers were used as raw materials. In order to improve the properties of the mixture, both in early age and hardened gypsum pastes, this study assessed whether an alternation in the misture proportion would yield a reduction in the absorption rate and an increase in the compression resistance, with consequent expansion of its use as an alternative material in civil construction in the production of modular panels to seal. Different types and quantities of resins were added in the water before mixing with the plaster. Laborstory tests were carried out to determine the workability of the gypsum paste, the initial and final setting time values, the absorption rate and compression resistance. Using the scanning electron microscopy, it was possible to analyze the microstructure of gypsum paste and comfirm the data obtained in laboratory tests of absorption and compression resistance. Two mixtures with additives were more relevant to the proposed objectives for this work. The results indicated that the addition of silicone, which is a commercial product, provided a decrease in the plaster absortion rate of 75%, when compared to mixture without silicone. However, their addition reduced the compression resistance of the material. The combined addition of silicone and Glenium 3200 HES yielded a reduction in water/plaster ratio of 30%, increasing the compression resistance ...

No Brasil, as atividades da construção civil são motivos de preocupação para os líderes ambientais, principalmente em relação à geração e à gestão dos resíduos da construção. Diante da necessidade de desenvolvimento sustentável nesse setor, a inovação tecnológica torna-se uma importante ferramenta para a minoração do impacto ambiental. Baseado nos princípios da produção mais limpa (P+L), o objetivo deste trabalho foi colaborar para o desenvolvimento da inovação tecnológica na construção civil, visando à redução dos resíduos gerados em obra. Utilizou-se como matéria-prima o gesso, água e polímeros, objetivando a melhoria nas propriedades deste material, tanto no estado fresco quanto no estado endurecido, como a redução da absorção e aumento da resistência à compressão, com conseqüente ampliação de sua utilização como material alternativo na construção civil na produção de painéis modulares de vedação. Diferentes tipos e quantidades de polímeros foram adicionados na água de amassamento do gesso para a realização de ensaios de laboratório que determinaram a trabalhabiblidade da pasta, os tempos de início e fim de pega, a taxa de absorção e a resistência à compressão axial. Pela microscopia eletrônica de varredura, foi possível analisar a microestrutura das pastas confeccionadas e confirmar os dados obtidos nos ensaios de absorção e resistência à compressão axial. Dois traços com presença de aditivos se destacaram em relação aos objetivos propostos neste trabalho. Os resultados indicam que a presença de Silicone, que é um produto comercial, proporcionou redução na taxa de absorção do gesso, de 75%, se comparado com traço branco de análise. No entanto, sua presença não influenciou significativamente na resistência à compressão do material. A adição combinada de Silicone e Glenium 3200 HES possibilitou a redução de 28% na relação água/gesso, aumentando...
Keywords: Sustainable development; Cleaner production; Civil construction; Gypsum; Wastes; Desenvolvimento sustentável; Construção civil; Gesso; Resíduos; Produção mais limpa